Development of a Data Reporting System for Monitoring Cannabis-Related Patients in Health Region 8 - พุดหล้า พัฒนรัฐ (Journal of Health Science of Thailand, 2025)
This research focused on developing a reporting system for real-time surveillance of patients using cannabis in Health Service Region 8. The objectives was to develop a real-time patient surveillance reporting system. The development process was divided into two phases. Phase 1 involved studying relevant theories, laws, impacts, and ICD-10 codes related to cannabis use. Phase 2 focused on studying and developing an information system, divided into two parts: (1) analyzing existing information systems and databases by utilizing data from the Data Center, which stores HIS (hospital information system) data from all hospitals in Region 8, extracting cannabis-related disease data, including diseases caused by cannabis; (2) developing a reporting system as an information system, following the software development lifecycle (SDLC). The reporting system included various features, such as regional patient overviews, province-level data, hospital-level data, daily reports, cumulative patient numbers, trends, age-group data, and gender-based data. The development of this real-time reporting system allows stakeholders involved in cannabis-related Service Plans at the regional, provincial, and hospital levels to monitor trends, forecast impacts and analyze data efficiently. Administrators can utilize the information for effective planning and policymaking. The study also suggests that this reporting system model can be further applied to other disease groups by utilizing specific ICD-10 data to develop tailored reporting systems or dashboards for monitoring various health concerns in real-time.